Influence of adjacent crop type on occurrence of California ground squirrels on levees in the Sacramento Valley, California - Michael C. McGrann; Dirk H. Van Vuren; Miguel A. Ordeñana (Wildlife Society Bulletin)
ABSTRACT In the Sacramento Valley in California, USA, burrowing activities of California ground squirrels (Otospermophilus beecheyi) on levees pose a threat to human safety and property by potentially compromising levee integrity during a flood event. Ground squirrel occurrence on levees is influenced by habitat features on the levee itself, but occurrence also might be influenced by food availability in adjacent areas. During June through September 2012, we evaluated the association between the occurrence of ground squirrels on levees and 5 common land‐use types adjacent to levees: perennial nut crops, perennial fruit crops, annual crops, rice, and grassland. Using burrow entrances as an index of ground squirrel occurrence and abundance, we found that ground squirrel occurrence was highest on levees adjacent to perennial nut and fruit crops and lowest adjacent to rice and grassland. Additionally, the number of burrow entrances on levees increased with percent cover of perennial nut crops on adjacent land. Our findings highlight the importance of a landscape perspective in managing human–wildlife conflicts, and will assist levee managers in prioritizing those reaches most at risk from infestation by ground squirrels, for inspection during routine maintenance, or for monitoring during a flood event. Further, opportunities might arise to coordinate with local landowners to establish crops adjacent to levees that are least attractive to ground squirrels. © 2013 The Wildlife Society.